2022
DOI: 10.21203/rs.3.rs-1857506/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification and functional exploration of Ferroptosis and Immune Related Long Non-Coding RNA in Inflammatory bowel disease

Abstract: Background:Inflammatory bowel disease (IBD) is an idiopathic intestinal inflammatory disease involving ileum, rectum and colon, including ulcerative colitis (UC) and Crohn's disease (CD).The etiology is complex, and immune dysfunction is considered to be the final pathological result. Methods:We constructed a lncRNA-mRNA regulatory network based on ferroptosis-related and immnue-related differentially expressed lncRNAs in IBD. Results: We identified 6 differently expressed lncRNAs associated with of ferroptosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…In a similar study, the analysis of 97 Uc and 75 cd samples alongside 22 normal controls revealed six differently expressed long non-coding RNAs (lncRNAs) associated with ferroptosis and immunity in IBd. A constructed lncRNA-mRNA regulatory network further identified potential miRNAs and transcription factors based on trans and competing endogenous RNA mechanisms, concluding that ferroptosis and immune-related lncRNA are involved in the regulation of aberrant immune response in IBd (59). The implication of ferroptosis in IBd pathology, as outlined above, is illustrated in Fig.…”
Section: Role Of Ferroptosis In the Pathogenesis Of Ibdmentioning
confidence: 87%
See 1 more Smart Citation
“…In a similar study, the analysis of 97 Uc and 75 cd samples alongside 22 normal controls revealed six differently expressed long non-coding RNAs (lncRNAs) associated with ferroptosis and immunity in IBd. A constructed lncRNA-mRNA regulatory network further identified potential miRNAs and transcription factors based on trans and competing endogenous RNA mechanisms, concluding that ferroptosis and immune-related lncRNA are involved in the regulation of aberrant immune response in IBd (59). The implication of ferroptosis in IBd pathology, as outlined above, is illustrated in Fig.…”
Section: Role Of Ferroptosis In the Pathogenesis Of Ibdmentioning
confidence: 87%
“…Studies have indicated that the fundamental characteristics of ferroptosis, including increased lipid peroxidation, the depletion of GSH, the inactivation of GPX4 and elevated iron deposition, are manifested in the inflamed intestinal tissue of patients with IBd and in animal models of IBd (19,58,59). Ferroptosis is involved in IBd, particularly intestinal epithelial cell death (5).…”
Section: Role Of Ferroptosis In the Pathogenesis Of Ibdmentioning
confidence: 99%